Rice Farming Performance for Sustainable Agriculture and Food Security in West Kalimantan - Nurliza Nurliza; Eva Dolorosa; Abdul Hamid A. Yusra (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
For more than three decades, domestic rice production was not able to meet its growing demand and showed in poor performance. This research aims to analyze the performance of rice farming in West Kalimantan. The research was conducted using descriptive methods through interviews. The data was analyzed to describe farmer personal character, skill and knowlwdge, risk analysis, and technical efficiency employing stochastic frontier model.  This study proved that farmer had 3 to 6 years of pupilage attainment; used rainfed; widely used Ciherang seeds; most of them had 0.25-1.25 ha; only 20% of rice farming could achieve over 6.5 tons/ha. The distribution of technical efficiency showed that only 17.41% of rice farmer is able to achieve sufficient; while 60-70% of technical efficiency is achieved by 30.37% of rice farmer. However, the risk of production, prices, and income each was than 0.5.